(untitled) (Proceedings of International Educators Conference, 2023)
Language is the main means of communication, it is difficult to imagine the existence and development of human society. Today, at a time when great changes are taking place in our world, the demand for learning foreign languages ​​is increasing in our country. the study of the English language is very deep. With the initiatives of our President, English is widely taught in all educational fields. The use of technology in the process of learning English is giving effective results.